In Vitro Antifungal Activity of Eco-Enzyme Derived from Horticultural Organic Waste Against Candida albicans - Lubis, Najla; Ate Tarigan, Ruth Riah; Hayati, Dwi (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
This study aimed to evaluate the antifungal activity of eco-enzyme (EE) derived from various horticultural organic wastes against Candida albicans. Two formulations were prepared: Bioz1 (pineapple peel, orange, papaya, starfruit, kuini, and mango) and Bioz2 (pineapple, orange, banana corm, noni, and kuini). Both were fermented for 100 days. The antifungal activity was tested in vitro using the disc diffusion method at concentrations of 1:0, 1:10, 1:50, and 1:100 (EE: distilled water). Results indicated that Bioz1 at 1:50 exhibited the highest inhibition zone (7.38 mm, medium category), while Bioz2 at 1:0 showed the strongest activity (8.16 mm, medium category). Dilution at 1:10 in Bioz2 was the most effective concentration for inhibiting fungal growth. These findings highlight the potential use of eco-enzyme as an environmentally friendly natural disinfectant against pathogenic fungi